Event-Related Brain Potentials: Laplacian Transformation for Multichannel Time-Frequency Analysis - Bianchi, A. M.; Locatelli, T.; Mainardi, L. T.; Cursi, M.; Comi, G.; Cerutti, S. (Methods of Information in Medicine, 2000)
During a visual-motor task the movement strategies and the learning processes are investigated. A group of 10 normal young volunteers underwent the experiment. The EEG signal was recorded through the 10-20 acquisition system during the execution of a task after a visual input. Each subject repeated the movement several times in three different conditions: i) without knowledge of the performance; ii) with visual feedback; iii) with knowledge of the result. The signal was transformed through Laplacian operator in order to eliminate the spurious coherence and then time-variant coherence was calculated. Different trends of the coherence function have been evidenced in subjects learning and not learning the better movement strategy. In particular, relations have been found between frontal, central and occipital electrodes in medium and high frequency ranges.
Keywords: Event-Related Potentials; Laplacian Transformation; Bivariate Time-Variant Spectral Analysis